Wheelchair housing design guide - Horn, Michelle; Smith, Jacqui; Runnalls, Jacquel; Sheehan, Kate
Filled with practical advice and design considerations, this invaluable guide provides all the information you need to design good quality, accessible housing for wheelchair users.